THE ROLE OF GIVING VIRGIN COCONUT OIL FOR HEALING PERINEUM WOUNDS IN POST-PARTUM MOTHERS - Suryati Romauli; Yeni Whardani (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
Background: The process of childbirth can cause perineal injuries. Efforts are being made in healing perineal wounds with standard techniques of normal delivery care. The latest developments in wound care such as the provision of Virgin Coconut Oil (VCO) can accelerate the wound healing process. Objective: This study aims to determine the effect of giving Virgin Coconut Oil on perineal wound healing in post partum mothers. Methods: This type of research is a quantitative experiment with a quasi-experimental design. The population was post partum mothers as many as 30 people consisting of an intervention group of 15 people with VCO administration and a control group of 15 people with standard techniques of normal delivery care. Data were obtained using an observation sheet with an observation time of 6 days on wound healing and analyzed using an independent T-test. Results: The results showed that the healing time of perineal wounds with the standard technique of Normal Childbirth Care averaged 8 days. There is an effect of giving VCO on the duration of perineal wound healing with an average speed of healing for 6 days. Conclusion: It was found that there was an effect of giving Virgin Coconut Oil on the healing of perineal wounds in post partum mothers. Keywors : Virgin Coconut Oil, Perineum Wound, Post Partum